Implementasi EOQ (Economic Order Quantity) Untuk Perencanaan Dan Persediaan Pipa HDPE di PDAM Tirta Mayang Kota Jambi - Agus Topo Subekti (LPPM Politeknik Jambi, 2021)
The problem in this research is how to forecast HDPE pipe supply orders at PDAM Tirta Mayang Jambi using the Economic Order Quantity (EOQ) method ?. The purpose of this study was to determine the Forecasting of HDPE Pipe Supply Orders at PDAM Tirta Mayang Jambi using the Economic Order Quantity (EOQ) method. The research method used in this research is descriptive method. According to Nazir (2011),